Analisis Bauran Pemasaran Terhadap Keputusan Pembelian Buah Melon di Super Indo Ngesrep, Kota Semarang - Sitompul, Putri Ruth Aprilia; Mukson, Mukson; Handayani, Migie (Universitas Galuh, 2025)
Melon is the holticultural that is popular with people because of its distinctive taste and aroma. The aim of the research was to identified purchasing decision process and analyze the influence of marketing mix on the decision purchase melons at Super Indo Ngesrep. The research was carried out in May-June 2024. The research location was in Super Indo Ngesrep, Semarang. The research method was case study. Sampling was taken by accidental sampling of 100 respondents who had bought melons at Super Indo Ngesrep, Semarang . Data analysis method used descriptive and linear regression. Product, price, location and promotion variables simultaneously influence purchasing decisions. The product, price and location variables have a partial influence on purchasing decisions, while the promotion variable has no partial influence on the decision to purchase melons at Super Indo Ngesrep, Semarang City.